Insomnia and HRQoL of Indonesians with Chronic Pain: The Role of Catastrophizing and Anxiety - Shabrina, Fariza Nur; Asih, Sali Rahadi (Psychological Research on Urban Society, 2021)
Insomnia and chronic pain share the same catastrophizing cognitive tendency. The high prevalence of insomnia and chronic pain was found in the urban population. Seeing the interaction between both in influencing individuals is imperative. Most studies in insomnia and pain are conducted in the Western population, with little to no research conducted in Indonesian urban population. As a part longitudinal chronic pain study, this research explored (a) the mediating role of pain catastrophizing in linking insomnia with health-related quality of life (HRQoL) and (b) the moderating role of anxiety trait in influencing the mediation within Indonesian adults with chronic pain. The data were gathered through self-administered online questionnaires, and the moderated-mediation analyses were conducted at the beginning phase of the longitudinal study. The results from 415 participants validated that pain catastrophizing partially mediated the relationship between insomnia and HRQoL. Furthermore, no significant moderating effect of anxiety trait was found. People with insomnia showed rumination, worry, and dysfunctional beliefs regarding their sleep, which generalized into catastrophic thoughts regarding their pain experience. This pain catastrophizing in turn influenced the HRQoL. Interventions that simultaneously target both catastrophic thoughts in insomnia and pain would prove to be beneficial in mitigating pain among Indonesian adults.